The Unex Application as An English Interactive Learning Media : A Feasibility Study - Arifin Arifin; Eria Prajayanti; Muhammad Hasby; Muhammad Taufik; Desy Tri Anggarini (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to analyze the feasibility of Unex application as an interactive learning media in enhancing students' understanding of English texts. Unex stands for Understanding English Text application. The study used research and development (R&D) method with the ADDIE model. The subject of this research was eleventh-grade students at Health Vocational School of North Borneo that use android smartphones. The research instruments were questionnaires and validation sheets. The questionnaire was a media practicality questionnaire used to find out the practicality of the media used by teachers after a try-out of the Unex Application. Furthermore, Validation sheets were used to validate the Unex Application. The analysis technique used to explain the response is descriptive analysis, which involves calculating the total, average, percentage and then is adjusted and categorized into several categories. The result showed that the validation from media and material experts for the Unex application was 96% and 98.4%, and both were in very feasible categories. Also, the result from the media practicality was 92.8%. Therefore, the Unex application is well-developed as an English interactive learning media for students Health Vocational School of North Borneo. Moreover, the media and material in the Unex application were validated and declared with good scores and very feasible categories.